2023
DOI: 10.3389/fimmu.2023.1240747
|View full text |Cite
|
Sign up to set email alerts
|

The impact of exosomes derived from distinct sources on rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease that can induce joint deformities and functional impairment, significantly impacting the overall well-being of individuals. Exosomes, which are cellularly secreted vesicles, possess favorable biological traits such as biocompatibility, stability, and minimal toxicity. Additionally, they contain nucleic acids, lipids, proteins, amino acids, and metabolites, serving as mediators in cellular communication and information exchange. Recent studies have demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…We investigated the proteome of the MSC secretome with the goal of identifying a cocktail of proteins that can be used as a pharmaceutical drug to treat RA. A plethora of research on MSC-derived exosomes, siRNAs, and conditioned media exist, but very little is known about the proteome of the secretome [20,21,22]. Our results reveal the key therapeutic targets for RA and how hBMMSCs secretome proteins can interact with these targets to potentially ameliorate RA.…”
Section: Discussionmentioning
confidence: 81%
“…We investigated the proteome of the MSC secretome with the goal of identifying a cocktail of proteins that can be used as a pharmaceutical drug to treat RA. A plethora of research on MSC-derived exosomes, siRNAs, and conditioned media exist, but very little is known about the proteome of the secretome [20,21,22]. Our results reveal the key therapeutic targets for RA and how hBMMSCs secretome proteins can interact with these targets to potentially ameliorate RA.…”
Section: Discussionmentioning
confidence: 81%
“…Conjugated with curcumin and albumin, they demonstrated the ability to normalise inflammatory markers in a skin inflammation model that mimics psoriasis [173]. Studies on rheumatoid arthritis have demonstrated that, on the one hand, bone marrow-derived DC EVs exert an anti-inflammatory effect, recovering the arthritis through the MHC II complex; on the other hand, by combining the antibody anti-reactive oxygen species collagen type II with neutrophil-derived EVs, it can be possible to access the cartilage [174]. A potential natural drug for the treatment of Lupus Erythematosus (LE) is curcumin; in fact, B cell lymphoma-derived EVs, encapsulated with curcumin, exert anti-inflammatory activity in an LPS mouse model, paving the way for the use of this compound for the treatment of glomerulonephritis by LE [175,176].…”
Section: Evs As Drug Delivery Systemmentioning
confidence: 99%
“…Exosomes are small membrane-bound vesicles ranging in size from 30 to 100 nm. They originate from various cell types and participate in immune modulation as well as immune pathogenesis associated with RA [ 12 ]. Therefore, it is imperative to investigate the potential mechanisms through which RA-FLSs-EXO regulates RA for identifying therapeutic targets for this condition.…”
Section: Introductionmentioning
confidence: 99%